INDONESIAN NATIONAL IDENTITY MODEL: THE IMPORTANCE OF RELIGION, SELF-ESTEEM, AND RELATIONS BETWEEN GROUPS AMONG MUHAMMADIYAH STUDENTS - Moordiningsih Moordiningsih; Wahyu Rahardjo; Lisnawati Ruhaena; Zahrotul Uyun; Ninik Supartini (UIN Sunan Kalijaga, 2021)
National identity is a discourse that attracts a lot with diversity, religion, self-esteem, and relations between groups, both in the context of family and peers. The issue of national identity in Indonesia intersects with efforts to maintain the harmony of the nation's life through the various challenges of pluralism. This study aims to analyze the importance of religion, self-esteem, negative multicultural communication in the family and on campus, and attitudes towards multiculturalism towards national identity. The participants of this study is 456 Moslem students from the Javanese tribe-Indonesia. This study uses structural equation modeling (SEM) to build empirical constructs of Indonesian national identity models. The results show some interesting findings. First, the empirical model fits into a theoretical model which means that the importance of religion, self-esteem, attitudes towards multiculturalism, and inter-group relations are able to explain the national identity of Indonesians. Second, the attitude towards multiculturalism has the strongest role in affecting the identity of Indonesians, followed by self-esteem and the importance of religion. Thirdly, the negative content of communication of diversity in family and educational settings poorly affected attitudes towards multiculturalism.Keywords: Attitude Toward Multiculturalism, Importance of Religion, National Identity, Negative Multicultural Communication, Self-EsteemIdentitas nasional merupakan diskursus menarik yang banyak dikaitkan dengan keberagaman, agama, harga diri, serta relasi antar kelompok, baik dalam konteks keluarga dan teman sebaya. Persoalan identitas nasional di Indonesia beririsan dengan usaha menjaga keharmonisan kehidupan berbangsa dalam melewati berbagai tantangan kemajemukan yang ada. Penelitian ini bertujuan untuk menganalisis pengaruh pentingnya agama, harga diri, komunikasi tentang multikultural yang negatif di keluarga dan di kampus, sikap pada multikulturalisme terhadap identitas nasional. Partisipan penelitian ini berjumlah 456 orang mahasiswa beragama Islam yang berasal dari suku Jawa. Penelitian ini menggunakan structural equation modeling (SEM) untuk melakukan konstruksi empiris model identitas nasional orang Indonesia. Hasil penelitian memperlihatkan beberapa temuan menarik. Pertama, model empiris fit dengan model teoretik yang artinya bahwa pentingnya agama, harga diri,komunikasi antar kelompok, sikap pada multikulturalisme, mampu menjelaskan identitas nasional orang Indonesia. Kedua, sikap pada multikulturalisme memiliki peran terkuat dalam memengaruhi identitas nasional orang Indonesia diikuti oleh harga diri dan pentingnya agama bagi individu. Ketiga, isi komunikasi keberagaman yang negatif pada setting keluarga dan kampus berpengaruh secara negatif pada sikap terhadap multikulturalisme. Implikasi penelitian ini menunjukkan bahwa identitas nasional Indonesia dapat dibangun dengan mengembangkan sikap terhadap multikulturalisme yang baik, yaitu dengan cara membangun komunikasi antar kelompok, memperkuat konsep harga diri dan konsep keyakinan pentingnya agama masing-masing individu.Kata kunci: Sikap terhadap multikulturalisme, Pentingnya agama, Identitas nasional, komunikasi multicultural yang negatif, Harga diri